IMPORT SUBSTITUTION IN THE POWER ENGINEERING INDUSTRY - M. M. Balashov (Стратегические решения и риск-менеджмент, 2020)
This article discusses the issues of dependence of power engineering in the Russian Federation on imported equipment in general and in the field of gas turbine technologies. The paper describes the features of foreign-made equipment that is operated at the power facilities of the Russian Federation, identifies the countries that produce the installed foreign equipment in the power industry. Possible economic consequences for the energy-intensive industry from the implementation of the program for the modernization of generating equipment within the framework of the import substitution program are estimated. The forecast scenario of the impact of the coronavirus pandemic on power consumption in the UNEG and the program for the modernization of generating equipment is also presented.